Maintenance Management Framework for Conservation of Heritage Buildings in Malaysia - Idrus, Arazi; Khamidi, M. Faris; Sodangi, Mahmoud (Canadian Center of Science and Education, 2010)
Despite the enactment of the National Heritage Act and establishment of the National Heritage Department in Malaysia, many heritage buildings still remain in poor conditions with signs of serious building defects threatening their survival because Legislations related to heritage buildings in the country do not sufficiently address the issue of maintenance and its management in the conservation of heritage buildings thereby resulting to poor maintenance management practices which eventually lead to deterioration of the buildings. More so, despite the rhetoric of the significance of maintenance management in the conservation of heritage buildings in Malaysia, there is still inadequate guidance about how maintenance should be envisaged, managed and integrated with other key management activities in the context of heritage building conservation. This paper is part of an ongoing research aimed at developing a maintenance management framework for conservation of heritage buildings in Malaysia. The proposed conceptual framework will provide a holistic guidance and understanding of the maintenance management practices to be adopted in the conservation of heritage buildings in Malaysia. This would enable custodians of heritage buildings in Malaysia to evaluate their maintenance management practices in relation to best practices and be able to re-position their maintenance management approaches to best practice standard.